Experimental studies on the effect of airflow on oven temperature and product qualities in cake baking process - Mohamad Shahapuzi, Nur Syafikah; Taip, Farah Saleena; Ab. Aziz, Norashikin; Ahmedov, Anvarjon (Faculty of Engineering, Universiti Putra Malaysia, 2012)
Convection oven offers a uniform heating process by increasing airflow and circulating air inside oven chamber has overcome the static air and dominant radiant heat that encounter in conventional oven. Consequently uneven cooking and surface browning on the product can be avoided. Therefore, the purpose of this study is to investigate the effect of air flow on oven temperature and product qualities in cake baking process. Experimental study is conducted within two different baking conditions; with and without airflow in convective oven. The parameters measured are internal oven temperatures and internal cake temperature whereas the output product qualities are measured in terms of height increment, moisture content and texture properties. Significant differences can be seen on the oven operating temperature and the product itself such as internal temperature, percentage of height increment, percentage of final moisture content and texture properties. Baking process with airflow condition showed a uniform heat distribution in the oven chamber, higher heating rate of internal cake temperature (6.7°C/min compared to 3.9°C/min for without airflow condition) and higher percentage of height increment of cake (3.21mm/min compared to 2.88mm/min for without airflow condition). Nevertheless, weight loss further ensues if cake baking process carried out with the present of airflow, compared to heating without airflow which the baked cake retains higher percentage of moisture content.